2021
DOI: 10.1016/j.ssaho.2021.100211
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity and polarisation regarding COVID-19 and related risks – A thematic analysis of comments from an international survey

Abstract: COVID-19 represents a risk to people's life and societies in their current shapes and functions, with institutionalised responses redefining everyday life. Crises in society can induce fear and tensions that can unite and divide people, inducing acts of solidarity and polarisation. The study explored articulations of solidarity and polarisation in relation to the COVID-19 pandemic and related risks. A Foucault-inspired thematic analysis was pursued on qualitative data from an international survey about COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Besides the motivation to get vaccinated in order to protect others, intergenerational solidarity has manifested in various other forms following the outbreak of coronavirus. As Kaye (in Coffey 2020 ) points out, ‘[e]ver since the pandemic started, we’ve seen mutual aid groups springing out of the soil overnight’ where the young and able-bodied are providing assistance to their infirm and elderly neighbours, be it in terms of picking up and delivering food shopping and emergency parcels, providing medical supplies and arranging foodbank referrals, offering some digitally mediated company to those feeling lonely while in self-isolation, or simply maintaining corporeal distance to show respect towards the vulnerable (see also Ajana 2021 ; Stjernswärd and Glasdam 2021 ). At the same time, there is also a sense in which the pandemic has put to test intergeneration solidarity, as young generations are believed to have borne the brunt of the situation more than older generations.…”
Section: Data Results and Analysismentioning
confidence: 99%
“…Besides the motivation to get vaccinated in order to protect others, intergenerational solidarity has manifested in various other forms following the outbreak of coronavirus. As Kaye (in Coffey 2020 ) points out, ‘[e]ver since the pandemic started, we’ve seen mutual aid groups springing out of the soil overnight’ where the young and able-bodied are providing assistance to their infirm and elderly neighbours, be it in terms of picking up and delivering food shopping and emergency parcels, providing medical supplies and arranging foodbank referrals, offering some digitally mediated company to those feeling lonely while in self-isolation, or simply maintaining corporeal distance to show respect towards the vulnerable (see also Ajana 2021 ; Stjernswärd and Glasdam 2021 ). At the same time, there is also a sense in which the pandemic has put to test intergeneration solidarity, as young generations are believed to have borne the brunt of the situation more than older generations.…”
Section: Data Results and Analysismentioning
confidence: 99%
“…Instead, it contributed to the use of the word “solidarity” as a political statement, as being on “the right side of things”. This became particularly noticeable in the late stages of the pandemic in Germany, where the word “solidarity” was commonly used to frame demonstrations against COVID deniers, thereby creating a divide rather than a sense of general togetherness ( Häyry, 2020 ; Stjernswärd & Glasdam, 2021 ). This shows that solidarity is a diversified term that is used in various settings, as it lacks a commonly accepted, firm definition ( Prainsack & Buyx, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors lamented the failure of global solidarity in the context of the global distribution of scarce resources, such as COVID-19 tests or vaccines (e.g., Figueroa et al, 2021 ; Obinna, 2021 ; Sekalala et al, 2021 ; Syntia Munung, Ujewe, & Afolabi, 2021 ). On a more national or regional level, it was suggested that calls for solidaristic practices could sometimes also lead to polarization instead of social cohesion ( Chadwick, 2020 ; Stjernswärd & Glasdam, 2021 ). For instance, intergenerational solidarity might also turn into ageism once solidarity towards the elderly is exhausted ( Ayalon et al, 2020 ; Barrett, Michael, & Padavic, 2021 ; Barth et al, 2021 ; Ellerich-Groppe, Pfaller, & Schweda, 2021 ; Fraser et al, 2020 ).…”
Section: Theorymentioning
confidence: 99%
“…It has enabled lockdowns on an unprecedented scale and the social experiment of a public debate largely conducted digitally, through social media and newspaper websites, in a context of "post-normal science" (Waltner-Toews et al, 2020). Two years later, many European societies are strongly polarised and divided (Modgil et al, 2021;Neumann et al, 2021;Stjernswärd & Glasdam, 2021) and European integration has suffered a setback through movement restrictions (Devi, 2020) and "minimal support given to member states forcing each to take a unique approach," so that "national approaches dominated with some lesson learning only and few attempts to institute a global response to the pandemic" (Lilleker et al, 2021, p. 339). Paralleling the threats to the individual body with threats to the body politic, the prevalence of national approaches may reinforce nativist ideas and strongborder thinking and undermine the European community and integration (Bieber, 2020).…”
Section: Introductionmentioning
confidence: 99%